Seasonal Variation of Solid Waste Components in Ranya District, Iraq. (Raparin Journal of Humanities (RJH), 2020)
Municipal solid waste can be considered as one of the significant environmental issues in worldwide, as a result of industrial revolution, economic development and overpopulation. The current study focused on seasonal variation of solid waste production and composition. The study was conducted during winter and summer seasons in 2019. Solid waste samples were collected from the collector trucks from eight different zones in Ranya district. The results revealed that the average of total solid waste generation in the district estimated as (286.9 tons/day) and (1.108 kg-capita/days). The analysis of the waste content detected that the largest portion of the district solid waste is organic material which forming an average of 67.05%. Followed by cloth & textile, plastic, paper & cardboards, metal and glass, which their quantities are 11.93%, 8.19%, 7.12%, 3.05% and 2.65% respectively. The seasonal variation impacts on solid waste has been preserved obviously in this research study, more specifically in metal, glass and organic waste contents, which their quantities increased substantially from wet to dry season, (6.2 to 11.61 tons/day), (6.26 to 9.07 tons/day) and (177.5 to 207.62 tons/day) respectively. Moreover, the total generated solid waste magnitude of the district picked up changed from 268.37tones/day for wet season to 305.44tones/day for dry season.